Development of questionnaire on awareness and action towards symptoms and risk factors of heart attack and stroke among a Malaysian population - Abdullah Abdulmajid Abdo Ahmed; Abdulkareem Mohammed AL-Shami; Shazia Jamshed; Abdul Rahman Fata Nahas (BMC, 2019)
Abstract Background The awareness of symptoms and action towards heart attack and stroke is important to reduce the morbidity and mortality in both developed and developing countries. The aim of this study was to develop a questionnaire on awareness and action towards symptoms and risk factors of heart attack and stroke among lay public in Malaysia. The questionnaire was developed in both English and Bahasa Melayu. Methods Primarily the questions were generated in English. Face and content validity were performed by five experts in Pharmacy Practice and Medicine. A translation as per guidelines into Malay language was performed; followed by face-to-face interview of 96 lay public in Kuantan, Pahang, Malaysia. For internal consistency, reliability was assessed utilizing Cronbach's alpha. Results The mean ± SD of the awareness and action towards heart attack symptoms and risk factors was 65.52 ± 6.3, with a good internal consistency (Cronbach's alpha = 0.75), whereas the mean of the awareness and action towards stroke symptoms and risk factors was 61.93 ± 7.11, with an accepted internal consistency (Cronbach's alpha = 0.86). Conclusion The current validation research showed that the developed questionnaire is valid and reliable for assessing the awareness and action towards symptoms and risk factors of heart attack and stroke among lay public in Malaysia.